Urbanization and housing in Kuala Lumpur city centre : issues and future challenges - Shuid, Syafiee (2004)
Rapid urbanization during the 1970’s and 1980’s has shown greater impact to urban and housing development in Kuala Lumpur from the previous era. But during the 1990’s due to better economic condition and changing urban dwellers’ lifestyle had led to counter urbanization of development. According to cencus in year 2000, population of Kuala Lumpur are at 1.29 million people far below projection by Kuala Lumpur Structure Plan 2000 (1984) at 2.2 million people by year 2000. Draft Kuala Lumpur Structure Plan 2020 (2003) review recently, had acknowledged that the slow population growth as compared to projection was mainly due to out-migration of people for better and cheaper houses outside Kuala Lumpur city. Kuala Lumpur City Centre also known as Central Planning Area (CPA), being the heart of Kuala Lumpur City had experienced the population decline from 156,981 people in 1980 to 128,721 people in 2000. In term of housing in city centre, although the number of units had shown an increase from 29,562 units in the year 1990 to 31,106 units in 2000 but housing land use component had dropped from 390.58 hectares in 1984 to 254.88 hectares in 2000. It seems that the trends will continue in the future and further deteriorate the residential population in city centre if no drastic measures taken by the Kuala Lumpur City Hall (CHKL). Therefore this paper will look into the impacts of urbanization process in Kuala Lumpur with particular reference to housing sector especially in the city centre. Which includes an analysis of the current issues and trends of housing development and recommendations for more sustainable urban growth in Kuala Lumpur.